AB1300 Comorbidities in patients with rheumatic diseases in colombia. (12th June 2018) - Cuervo, F.M.; Santos, A.; Saldarriaga, E.L.; Rueda, J.C.; Angarita, I.; Peláez, I.; Forero, E.; Ramirez, J.; Toro, C.; Londono, J.
Abstract : Background: Patients with systemic autoimmune conditions often develop concomitant disease contributing to a higher mortality than in the general population. An early diagnosis and treatment is fundamental to improve the life expectancy of this population. Objectives: The objective of this study was to describe the frequency of comorbidities in patients with rheumatic diseases. Methods: Based on data from the population studied under the COPCORD strategy, in the prevalence of rheumatic disease in Colombia, the frequency of non-rheumatic diseases in patients with rheumatic diseases was described in 6 cities of Colombia (Bogotá, Medellín, Cali, Barranquilla, Bucaramanga and Cúcuta). Results: From a total of 4020 individuals, 2274 rheumatic patients were identified. Sixty nine percent of the Colombian patients with rheumatic disease (n=1571) had some comorbidity. The most frequent was hypertension (HBP) in 20, 95% (n=330), followed by migraine 19, 11% (n=300) and venous insufficiency 17, 69% (n=278). Seventeen percent had any mental disorders, of which, anxiety and depression were the most common (n=273). Other comorbidities like obesity (8, 1%), diabetes (5, 85%), heart disease (5, 79%) and cerebrovascular disease (1, 99%) were less common among rheumatic patients. The frequency of cancer was low 1.48% (n=23). Abstract AB1300 – Figure 1 Conclusions: Hypertension is the most common comorbidity in patients with rheumatic diseases in Colombia. Screening and diagnosis in early stages of HBP is important, since it is the main modifiable cardiovascular risk factor. The goals of pharmacological and non-pharmacological treatment are essential to reduce the risk of coronary heart disease, stroke and end-stage renal disease. Additionally, migraine is the second most frequent disease that affects the patient's quality of life. And venous insufficiency should be taken into account by primary care physicians in order to assure a complete health care assessment. Disclosure of Interest: None declared